Increased Risk of Hospital Admission for Asthma in Children From Short-Term Exposure to Air Pollution: Case-Crossover Evidence From Northern China - Zhao, Yakun; Kong, Dehui; Fu, Jia; Zhang, Yongqiao; Chen, Yuxiong; Liu, Yanbo; Chang, Zhen'ge; Liu, Yijie; Liu, Xiaole; Xu, Kaifeng; Jiang, Chengyu; Fan, Zhongjie (Frontiers in Public Health, 2021)
Background: Previous studies suggested that exposure to air pollution could increase risk of asthma attacks in children. The aim of this study is to investigate the short-term effects of exposure to ambient air pollution on asthma hospital admissions in children in Beijing, a city with serious air pollution and high-quality medical care at the same time. Methods: We collected hospital admission data of asthma patients aged ≤18 years old from 56 hospitals from 2013 to 2016 in Beijing, China. Time-stratified case-crossover design and conditional Poisson regression were applied to explore the association between risk of asthma admission in children and the daily concentration of six air pollutants [particulate matter ≤ 2.5µm (PM2.5), particulate matter ≤ 10µm (PM10), sulfur dioxide (SO2), nitrogen dioxide (NO2), carbon monoxide (CO), and ozone (O3)], adjusting for meteorological factors and other pollutants. Additionally, stratified analyses were performed by age, gender, and season. Results: In the single-pollutant models, higher levels of PM2.5, SO2, and NO2 were significantly associated with increased risk of hospital admission for asthma in children. The strongest effect was observed in NO2 at lag06 (RR=1.25, 95%CI: 1.06-1.48), followed by SO2 at lag05 (RR=1.17, 95%CI: 1.05-1.31). The robustness of effects of SO2 and NO2 were shown in two-pollutant models. Stratified analyses further indicated that pre-school children (aged ≤ 6 years) were more susceptible to SO2. The effects of SO2 were stronger in the cold season, while the effects of NO2 were stronger in the warm season. No significant sex-specific differences were observed. Conclusions: These results suggested that high levels of air pollution had an adverse effect on childhood asthma, even in a region with high-quality healthcare. Therefore, it will be significant to decrease hospital admissions for asthma in children by controlling air pollution emission and avoiding exposure to air pollution.